Surgical treatment of bilateral glossopharyngeal neuralgia. (2nd December 2018) - Ganaha, Sara; Grewal, Sanjeet S.; Cheshire, William P.; Reimer, Ronald; Quiñones-Hinojosa, Alfredo; Wharen, Robert E.
Abstract: Glossopharyngeal neuralgia (GPN) is a condition characterised by sudden, severe pain in the distribution of the glossopharyngeal nerve. It can be triggered by talking, yawning, coughing and swallowing. Classically, patients experience a unilateral lancinating and excruciating pain described as electrical shock-like pain in the areas around the ear, tongue, or the mandibular angle. Uncommon manifestations include cardiac arrhythmias and syncope during pain episodes. Surgery is indicated in refractory cases. Bilateral GPN is rare, and definitive surgical treatment for bilateral GPN has not yet been reported. In this case report, a young woman with bilateral GPN who underwent staged surgery bilaterally is described. She did not develop life-threatening cardiac abnormalities postoperatively.